Moral Self-Image (MSI) and Self-esteem (SE) Among Young adults - Raja Zeeshan Sarmad; Anam Naeem; Iffat Batool (Dialogue Social Science Review (DSSR), 2025)
The present research explored the relation between MSI and SE among young adults in Pakistan. The sample comprised 400 young adults (200 men & 200 women) with an age range 19 to 36 years (M = 29.1; SD = 7.6 years) through convenience sampling. Moral self-image scale (MSIS; Naeem, Batool,Tariq, & Khan, 2022) and Rosenberg self-esteem scale (Rosenberg, 1979) were administered. Correlational research design was used to explore the study variable and its associations. The result of the study revealed that Moral self-image was positively correlated with self-esteem (r = .65, p < .01). To explore the association between MSI and SE, a simple linear regression was conducted showed significant association between MSI and SE (β = .65, t =13.62, p < .001). To explore Gender differences, an independent sample t-test was conducted and the results of independent sample t test revealed that women scored higher on moral self-image then men [t (398) = -2.45, p<.05]. Results also revealed that women scored higher sub-dimensions of moral self-image includes generosity [t (398) = -2.77, p<.01], compassion [t (398) = -3.84, p<.001], and lawfulness [t (398) = -2.22, p<.05]. Although, no significant gender differences were observed on the variables of integrity [t (398) = -1.62, p < .n.s], forgiveness and social welfare [t (398) = -.57, p< .n.s], tolerance [t (398) = -.36, p < .n.s] and self-esteem [t (398) = -.68, p < .n.s] among young adults. The present study has its implication in clinical Psychology, personality assessment and educational setting.